Cinematic art from cinematography to digital diversity of forms and multiplicity of content Review Article (Zien Journal of Social Sciences and Humanities, 2022)
Film art, like the case of other arts, has witnessed great developments at all levels, but the specificity that cinematic art enjoys without other arts is its short life, as it is a recent discovery and did not go on to install its artistic foundations more than two centuries ago. The other thing worth mentioning is that art Film mainly depends on the technical side, so it is sure to be affected by the technical developments that the world has witnessed, so this art has witnessed great aesthetic, expressive and technical transformations and has become a wide field for experimentation in various fields , The film began with a technical discovery, the purpose of which was to study the effects of light and lenses, and soon turned into a tool for entertainment and entertainment, and then became a fertile field for thought, expression, propaganda and media, and soon became a great economic and commercial force, and film production continues to grow, develop and experiment and is able to interact with the development of life in all its fields